Investigating the mediating role of the meaning of life in the relationship between perceptions of parenting styles and teenagers’ optimism - Ataei Zanjaninejad, Zahra; Hejazi, Masoud; Sobhi, Afsaneh; Ahmadi, Mohammad Saeed (Applied Family Therapy Journal (AFTJ), 2022)
Aim: This research was conducted with the purpose of investigating the relationship between the perception of parenting styles and optimism with the mediating role of the meaning of life in the second secondary school students of Zanjan city. Research method: The descriptive research method is correlation type. The statistical population was 20,866 students of the second secondary school in Zanjan city in the academic year 2018-2019. According to Morgan’s table, 392 people, but to increase the validity of the findings, 400 people were selected and distributed by stratified random method. To collect data, the standard questionnaires of Alabama parenting (1991), Shier and Caro’s optimism (1985) and Stickerer et al.’s (2006) meaning of life questionnaires were used. Data were analyzed using SPSS24 statistical software and AMOS statistical software was used in structural equation modeling. Results: The findings showed that there is a significant relationship between perception of parenting styles and optimism (p<0.01). But there is no significant relationship between the perception of parenting styles and the meaning of life (p≥0.05). The meaning of life plays a mediating role in the relationship between parenting styles and optimism (p<0.01). Conclusion: It can be concluded that the perception of parenting styles plays a decisive role in creating optimism in children and the meaning of life can lead to optimism in children.